Herd Behavior as a Determinant of Students’ Choice of Major to Study in the University - Mahmoud, Ferial Alhaj (Islamic Guidance and Counseling Journal, 2026)
After graduation from secondary school, students face the decision of selecting a university major, which may be influenced by factors beyond personal preferences, including herd behavior. Although previous research has identified various social and contextual influences on major choice, limited attention has been given to herd behavior as a distinct psychological mechanism, and there remains a lack of culturally grounded instruments to measure this construct, particularly within Middle Eastern contexts. The aims of this study were to construct a scale for the herd behavior effect on students’ university major choice (HBMC) and to explore any differences in this effect according to gender and college. A ten-item scale developed by the researcher was administered to a sample of 1,254 students from six universities in Jordan.  Exploratory and confirmatory factor analyses confirmed the unidimensional structure for the HBMC scale, and its good psychometric properties (α = 0.953). The results also indicated significant gender differences in the herd behavior effect, in favor of males (F = 5.281, df = 1, p < 0.01). These results highlight the importance of psychological and vocational guidance programs to enhance secondary school students’ independent thinking in selecting their university major according to their inclinations, abilities, aspirations, and their plans of professional future, rather than blindly imitating of others.